2012
DOI: 10.1002/jbm.a.34361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microtopographic patterns on platelet adhesion and activation on titanium oxide surfaces

Abstract: This study systematically investigated the effects of microtopographic patterns of titanium oxide on platelet adhesion and activation in order to reveal the mechanisms of interactions between platelet and surface topography. Periodic arrays of groove and pillar patterns with dimensions ranging from submicron to several micrometers were fabricated by photolithography and deep reactive-ion etching on silicon substrates, followed by the sputter deposition of titanium oxide (TiO(2)). Platelet adhesion and activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 43 publications
3
41
1
Order By: Relevance
“…The protocol used to evaluate platelet adhesion is described in our previous report [28]. Briefly, to prepare platelet-rich plasma (PRP), whole blood was centrifuged (200g, 15 min) and the supernatant was collected.…”
Section: Platelet Adhesion and Activationmentioning
confidence: 99%
“…The protocol used to evaluate platelet adhesion is described in our previous report [28]. Briefly, to prepare platelet-rich plasma (PRP), whole blood was centrifuged (200g, 15 min) and the supernatant was collected.…”
Section: Platelet Adhesion and Activationmentioning
confidence: 99%
“…Our results show no significant differences in platelet responses (adhesion, aggregation, and activation) on NCD coatings with small grain sizes versus large grain sizes. The importance of considering nanotopography in hemocompatibility is highlighted by previous studies that have shown platelet responses are dependent on multiple surface topography characteristics, including surface feature size, 23,24,30,69,70 geometry, 69 aspect ratio, 23 density, 23,30 and roughness of the biomaterial surface. 29,69,71 NCD is an ideal biomaterial coating for blood-contacting devices due to its mechanical robustness, chemical inertness, high wear resistance, and biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of considering nanotopography in hemocompatibility is highlighted by previous studies that have shown platelet responses are dependent on multiple surface topography characteristics, including surface feature size, 23,24,30,69,70 geometry, 69 aspect ratio, 23 density, 23,30 and roughness of the biomaterial surface. 29,69,71 NCD is an ideal biomaterial coating for blood-contacting devices due to its mechanical robustness, chemical inertness, high wear resistance, and biocompatibility. 15,16,32,72 In this study, NCD coatings with different nanoscale grain sizes were successfully fabricated in a controllable and reproducible manner.…”
Section: Discussionmentioning
confidence: 99%
“…Ding et al. investigated titanium oxide pillars as well as grooves statically with human platelet‐rich plasma (PRP) for 45 and 60 min, respectively, in terms of activation and adhesion. After scanning electron microscopy (SEM), they concluded that structure distances should be within a range of 1.5–3 μm to avoid “bridging” between the structures and at the same time full contact of platelets to the surface.…”
mentioning
confidence: 99%
“…The chemical methods include all modifications of the material's chemistry as, for example, organic and inorganic coatings or bio-functionalization (9)(10)(11)(12)(13). Physical methods include all techniques which alter the surface properties by mechanical structuring of the surfaces, for example, random or regular structures in the micro-or nanometer range or the adjustment of a special roughness (3,7,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Ding et al…”
mentioning
confidence: 99%